ESWL RESULTS OF 31 PATIENTS WITH SYMPTOMATIC CHOLELITHIASIS - M. Refik MAS; Ayhan DİNÇ; A. Kemal GÜRBÜZ; Selahattin ERİKÇİ; Ümit ATEŞKAN; Kenan SAĞLAM; Y. BAYKAL; Tahir ÜNAL; Fikri KOCABALKAN (Turkish Journal of Gastroenterology, 2020)
-